A Study On Treatment Barriers Among Amphetamine-Type Stimulant (Ats) Drug Users In Malaysia - Shanmugam, Thorairaj (2022)
People who use amphetamine-type stimulant (PWUA) often hesitate to participate in treatment program, and may encounter various barriers while seeking treatment. This study sought to identify treatment barriers and gender differences in barriers (if any) that precluded PWUA from participating in drug treatment programs in Malaysia. Three hundred and eighty-six treatment inmates who were mandated to undergo rehabilitation for their ATS use history were recruited through convenience sampling from five drug rehabilitation centres (CCRCs) for this cross-sectional study. The study data was collected through face-to-face interviews by a trained student using the Treatment Barriers Questionnaire (TBQ) scale. The majority (83%, n=321/386) were males, only 17% (n=65) consisted of females. Most were ethnic Malays (95%, n=365/386), single (61%), and were employed (85%) prior to their confinement.